A randomized phase-II study of reirradiation and hyperthermia versus reirradiation and hyperthermia plus chemotherapy for locally recurrent breast cancer in previously irradiated area. (3rd April 2022) - Schouten, Daphne; van Os, Rob; Westermann, Anneke M.; Crezee, Hans; van Tienhoven, Geertjan; Kolff, M. Willemijn; Bins, Adriaan D.
Abstract: Background: In patients with inoperable local regional recurrences of breast cancer in previously irradiated areas, local control is difficult to maintain and treatment options are limited. The Dutch standard treatment for such recurrences is reirradiation combined with hyperthermia. Apart from enhancing the effect of reirradiation, hyperthermia is also known to improve local effects of chemotherapy like cisplatin. This randomized phase-II trial compares reirradiation and hyperthermia versus the same treatment combined with cisplatin. Patients and methods: From December 2010 up to January 2019, 49 patients were randomized, 27 in the standard arm and 22 in the combined arm. A total of 32 Gy was given in eight fractions of 4 Gy in 4 weeks, at two fractions per week. After January 2015, the radiation schedule was changed to 46 Gy in 23 fractions of 2 Gy, at five fractions per week. Hyperthermia was added once a week after radiotherapy. The combined arm was treated with four cycles of weekly cisplatin 40 mg/m 2 . Results: Complete response rate was 60.9% in the standard arm and 61.1% in the combined arm ( p  = 0.87). Partial response rate was 30.4% in the standard arm and 33.3% in the combined arm ( p  = 0.79). One-year overall survival was 63.4% in the standard arm and 57.4% in the combined arm. One-year local progression-free interval was 81.5% in the standard arm and 88.1% in the combined arm ( p  = 0.95). Twenty-five percentage of patients in the standard arm experienced grade 3 or 4 acute toxicity and 29% of patients in the combined arm ( p  = 0.79). Conclusion: No potential benefit could be detected of adding cisplatin to reirradiation and hyperthermia in patients with recurrent breast cancer in a previously irradiated area. With or without cisplatin, most patients had subsequent local control until last follow-up or death.